2013
DOI: 10.1021/np300894y
|View full text |Cite
|
Sign up to set email alerts
|

Leporizines A–C: Epithiodiketopiperazines Isolated from an Aspergillus Species

Abstract: Three new compounds named leporizines A-C have been isolated from an Aspergillus sp. strain. Their structures were elucidated by analysis of 1D and 2D NMR spectra. Leporizines A and B were isolated during dereplication of hits from a high-throughput screening campaign for correctors of the cystic fibrosis transmembrane conductance regulator (CFTR), and leporizine C was isolated while preparing additional material for characterization of leporizines A and B. CFTR activity observed for leporizines A and B was hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“… CBS 650.74 T A. leporis Antibiotic Y ( Frisvad & Samson, 2000 ), kojic acid ( Frisvad & Samson, 2000 ), leporins ( TePaske et al . 1991 ), leporizines ( Reategui et al . 2013 ), pseurotin A ( Frisvad & Samson, 2000 ) Antibiotic Y, clavatols, 7-hydroxytrichothecolone?, kojic acid, leporine A, leporiziznes, paspalines, pseurotin A CBS 151.66, CBS 349.81, ATCC 76617, IBT 16309, IBT 16585 A. luteovirescens Aflatoxin B 1 , B 2 , G 1 , G 2 ( Pildain et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… CBS 650.74 T A. leporis Antibiotic Y ( Frisvad & Samson, 2000 ), kojic acid ( Frisvad & Samson, 2000 ), leporins ( TePaske et al . 1991 ), leporizines ( Reategui et al . 2013 ), pseurotin A ( Frisvad & Samson, 2000 ) Antibiotic Y, clavatols, 7-hydroxytrichothecolone?, kojic acid, leporine A, leporiziznes, paspalines, pseurotin A CBS 151.66, CBS 349.81, ATCC 76617, IBT 16309, IBT 16585 A. luteovirescens Aflatoxin B 1 , B 2 , G 1 , G 2 ( Pildain et al .…”
Section: Resultsmentioning
confidence: 99%
“…A. leporis , not being able to produce aspergillic acid, produces leporins more readily. Apart from kojic acid and leporins, A. leporis produces leporizines A, B and C ( Reategui et al. 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…7). 89 Ten new carbazole alkaloids, claulansines A (199), B (200), C (201), D (202), E (203), F (204), G (205), H (206), I (207), and J (208) were isolated from the stems of Clausena lansium. Compounds 199, 204, and 206-208 showed selective neuroprotective effects (Fig.…”
Section: Non-tryptaminesmentioning
confidence: 99%
“…Thus, the soft rot pathogen is an aporia and a bottle-neck for developing the industrial chain of Amorphophallus rivier in China [ 4 ]. The fungal genus of Aspergillus was widely distributed in soil, plant and ocean environments, and attracted the attention of chemists and pharmacologists because of their enormous metabolites production potential and multifariously biological activities [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The investigation into the chemical structure and bioassay diversities of the endophytic fungi around the Three Gorges area were performed, we found that the crude extract of the endophytic fungus, Aspergillus versicolor (No.…”
Section: Introductionmentioning
confidence: 99%